Answer:
therefore the value of x = 3 and y = -2
Step-by-step explanation:
using substitution method in solving the following equation
let
y = -x + 1 ........................ equation 1
y= 2x– 8........................... equation 2
substitute for 1 in equation 2 i.e put the value of y in equation 1 to value of y in equation 2
y= 2x– 8........................... equation 2
-x + 1 = 2x - 8
by collecting the like terms
1 + 8 =2x + x
9 = 3x
divide both sides by 3
we have
9/3 = 3x/3
3 = x
therefore x = 3
put x = 3 in equation 1
y = -x + 1 ........................ equation 1
y = -(3) + 1
y = -2
therefore the value of x = 3 and y = -2
to check if your answer is correct
put the value of x and y in either equation one or 2
y= 2x– 8........................... equation 2
-2 = 2(3) - 8
-2 = 6 - 8
-2 = -2 ......................... proved